Why is Unemployment High in the Philippines? - Brooks, Ray (IMF Working Papers; Working Paper ;, 2002)
Unemployment has remained high in the Philippines, at almost twice the level of neighboring countries, despite relatively fast employment growth in the past decade. Employment growth was not sufficient to reduce unemployment because of rapid population growth and increased labor force participation. This paper shows that Philippine employment growth and unemployment declines were positively correlated with real GDP growth and, to a lesser extent, negatively with the real minimum wage. The key policy implications are that higher economic growth and moderation of increases in the real minimum wage are required to reduce unemployment.